2021
DOI: 10.3389/fceng.2021.631397
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Environmental Life Cycle Assessment of the Combustion of Ammonia/Methane Fuels in a Tangential Swirl Burner

Abstract: Ammonia has been proposed as a replacement for fossil fuels. Like hydrogen, emissions from the combustion of ammonia are carbon-free. Unlike hydrogen, ammonia is more energy dense, less explosive, and there exists extensive experience in its distribution. However, ammonia has a low flame speed and combustion emits nitrogen oxides. Ammonia is produced via the Haber-Bosch process which consumes large amounts of fossil fuels and requires high temperatures and pressures. A life cycle assessment to determine potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Valera-Medina [16] Ammonia blends with methane for heat generation. Most studies conclude that current technologies used to produce green ammonia need to be improved.…”
Section: Razon Andmentioning
confidence: 99%
See 3 more Smart Citations
“…Valera-Medina [16] Ammonia blends with methane for heat generation. Most studies conclude that current technologies used to produce green ammonia need to be improved.…”
Section: Razon Andmentioning
confidence: 99%
“…Their study focused on alkaline units, denoting that there is still work to do to improve cell lifetime, power densities, and fuel consumption for less impactful devices. Further work was presented by Razon and Valera-Medina [16], who studied ammonia in gas turbines. Blends of ammonia-methane were evaluated, with results showing that ammonia produced from nuclear or wind energy could potentially support global decarbonisation with a −27% to −32% reduction in global warming potential.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, comparisons with other fuels have shown that ammonia's versatility can enable its use for combustion or in fuel cell devices [4], potentially delivering greater hydrogen quantities than other options (i.e., liquid organic hydrogen carriers, LOHC) at lower costs. Similarly, life cycle analyses denote how ammonia-fuelled systems present great potential to deliver green, sustainable stranded hydrogen [5][6][7] whilst reducing greenhouse emissions in support of the reduction in large carbon footprint scenarios.…”
Section: Introductionmentioning
confidence: 99%